KEARIFAN LOKAL DI BALIK MITOS LEMBU PUTIH DI DESA TARO, GIANYAR - Pujaastawa, I.B.G. (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract The study tried to reveal the local wisdom which resided behind the myth of white ox at Taro village, Gianyar. According to conception of social confidence at Taro village, existence the white ox in the village represent the holy animal owned by deity who protecting their life. On that account, the society always treat it very respectively and prohibiting to exploit it for secular purposes. The phenomenon tried to comprehended by using cultural materialism approach to expose the rationality which hidden behind the myth of the white ox. Currently, according to view of cultural materialism, stated that behind the traditional society confidence system often there are rational logics as form of adaptation response to economic conditions and ecology faced. This study found that behind myth about the white ox in Taro village consisted economic benefit and ecology in the form of, (1) distribution of agriculture area and fee for the who herds, (2) as mechanism of pest control and (3) as mechanism of genetic purification of the white ox as endemic animal.
Keywords: Key words : local wisdom, white ox, myth, ecology